2013
DOI: 10.1016/j.rmed.2013.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in the elderly: The role of exhaled nitric oxide measurements

Abstract: Summary Asthma in the elderly is poorly understood because only a small minority of asthma studies have investigated this patients group. Fractional Exhaled Nitric Oxide (FENO) has been extensively studied in children and adults with asthma, but little is known about FENO in elderly asthmatics. We studied the role of serial measurements of FENO in elderly subjects with asthma. Thirty stable asthmatics 65 years old and older were followed for one year with evaluations at baseline and every three months. We look… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 8 publications
2
9
1
1
Order By: Relevance
“…Similar to other studies [10], including ours of FENO in elderly asthmatics [11], we found no association between FENO and FEV 1 , FEV 1 /FVC, or FEF 25-75% throughout the study period.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to other studies [10], including ours of FENO in elderly asthmatics [11], we found no association between FENO and FEV 1 , FEV 1 /FVC, or FEF 25-75% throughout the study period.…”
Section: Discussionsupporting
confidence: 90%
“…Exhaled nitric oxide fraction ( F eNO ) has been proposed as a marker of airway eosinophilic inflammation; therefore, it is plausible that it could play a role in the diagnosis of asthma in elderly patients. Unfortunately, data that have specifically addressed this issue are limited and mostly influenced by the use of inhaled corticosteroids (ICS) [ 37 ]. Of note, in healthy subjects, F eNO levels appear to show a triphasic shape with an ascendant loop during adolescence, a plateau in adults and a linear increase in the elderly until age 80 years [ 38 ].…”
Section: Diagnosis Of Asthma In Advanced Agementioning
confidence: 99%
“…In elderly patients with asthma, we have previously studied the role of exhaled nitric oxide measurements and vitamin D [ 2 , 3 ]. Indeed, there is growing interest in the possible role of dietary supplements (e.g., vitamins and methyl donors) in asthma [ 4 , 5 ].…”
Section: Resultsmentioning
confidence: 99%